2021
DOI: 10.1111/bjet.13095
|View full text |Cite
|
Sign up to set email alerts
|

Promoting children's inquiry performances in alternate reality games: A mobile concept mapping‐based questioning approach

Abstract: Active inquiry plays a key role in science education. To facilitate children's motivation, alternate reality games are applied to engage children actively in inquiry in authentic learning contexts. However, the complexity of real‐world contexts and the ambiguity of game puzzles increase the difficulty for children to conduct effective inquiries. To achieve successful inquiry‐based learning, concept mapping is an effective learning strategy to guide children to organise related information as well as to brainst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 40 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…In terms of learning achievement, the finding is in line with the previous research which found that learning with concept mapping helped students effectively associate new learning experiences with prior knowledge in an organized manner, which could help them memorize and comprehend the learning content (Chiou, 2008; Hwang, Shi et al., 2011; Jonassen et al., 1998; Novak, 1990). The use of AI, such as the IR system, in educational settings, enables teachers to design new learning activities using the systems to provide students with opportunities to learn in a convenient and innovative manner (Freeman & Jessup, 2004; Hwang, Zou et al, 2020; Liang et al., 2021). In this study, the IR system helped the students to identify the plants found in real‐world environments using IR technologies and online databases.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of learning achievement, the finding is in line with the previous research which found that learning with concept mapping helped students effectively associate new learning experiences with prior knowledge in an organized manner, which could help them memorize and comprehend the learning content (Chiou, 2008; Hwang, Shi et al., 2011; Jonassen et al., 1998; Novak, 1990). The use of AI, such as the IR system, in educational settings, enables teachers to design new learning activities using the systems to provide students with opportunities to learn in a convenient and innovative manner (Freeman & Jessup, 2004; Hwang, Zou et al, 2020; Liang et al., 2021). In this study, the IR system helped the students to identify the plants found in real‐world environments using IR technologies and online databases.…”
Section: Discussionmentioning
confidence: 99%
“…A concept map is a visual organizer of knowledge that helps students enrich their understanding of a particular domain ( Novak and Gowin, 1984 ). CM was found useful in enhancing 10th-grade students’ scientific inquiry course performance ( Huang et al, 2022 ); improving ninth-grade students’ learning achievement ( Li et al, 2021 ); affecting children’s learning achievement, critical thinking, and learning attitude ( Liang et al, 2021 ); enhancing fifth graders’ (especially those with higher levels of critical thinking tendency) learning performance ( Hwang et al, 2021a ); and in improving eighth-grade students’ learning achievement, critical thinking tendency and problem-posing quality ( Hwang et al, 2021b ). A recently published systematic review on the roles, applications and trends of concept map-supported learning ( Chang et al, 2022 ) showed the benefits of using concept maps to facilitate knowledge construction in collaborative learning and improve learning achievement and motivation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Critical thinking can be implemented with the inquiry learning model (Sutiani, Situmorang, & Silalahi, 2021). Inquiry is one of the common processes carried out by students to find or understand information (Liang, Hsu, & Hwang, 2021). Inquiry activities can be used to train students' thinking skills and develop knowledge in dealing with situations or problems associated with exercises from a series of questions learning science in improving students' critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%